Sewage sludge-based organomineral fertilizer: A pathway to enhanced soil fertility and chickpea production - Athos Rodrigues Soares Viana; Rodinei Facco Pegoraro; Regynaldo Arruda Sampaio; Luiz Arnaldo Fernandes; Leidivan Almeida Frazão; Cândido Alves da Costa; Verônica Aparecida Santos Ferreira Soares (International Journal of Recycling of Organic Waste in Agriculture, 2024)
Purpose: Sewage sludge compounds possess physical and chemical attributes that make them well-suited for formulating fertilizers intended for agricultural purposes. Within this framework, the research aimed to assess the effects of utilizing organomineral fertilizers derived from sludge on soil fertility and chickpea yield.